El Método Doman En El Desarrollo del Lenguaje En Infantes del Sub Inicial 2 de La Escuela de Educación Básica Benjamín Franklin, Ciudad De Riobamba - Freire Pico, Domenica Freire (2024)
The primary goal of this research is to propose the Doman method for language development in infants of Sub-Inicial 2. Recognizing that language is a fundamental pillar for human beings stresses its paramount importance in early childhood education. Considering the difficulties that can arise in its development in the initial ages also highlights the potential of the Doman method to address these challenges, underscoring the significance and relevance of our research. Furthermore, research was carried out with a quantitative approach. It also has a nonexperimental design because none of the variables were manipulated; the type of research by the objective, the basic, the place of field, and the level of scope are descriptive, and the information collected is a bibliography. To verify its efficiency, an observation sheet was made through which the learning achieved with the use of this method will be observed; the population to which it was applied were the children of sub-initial 2 of the Benjamin Franklin Development Center, a process of analysis and tabulation was applied with the results obtained. It was concluded that using various methods, techniques, and different skills is very useful for children in Early Childhood Education to achieve an adequate process in their language. The potential of the Doman method was reaffirmed, providing reassurance and confidence in its effectiveness for a meaningful teachinglearning process.